Dampak Wifi Bagi Pemuda Terhadap Sosial Keagamaan Desa Cibubukan Aceh - sarkawi sarkawi (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2021)
Technological advances have brought so many changes, these changes are not only in the world of education, including the world of business, culture and social society, technological advances are so fast entering all corners, including the internet which is part of the development of these technologies. Data packages are not a problem in order to be able to access the internet and social media such as facebook, whatsapp, messenger, twitter and others, it can almost be said that the internet is now a necessity, lately several village governments provide free wifi networks for their people, including villages fuss. This research is a field research, which is based on the facts and facts found, the data collection tools are observation, interviews, questionnaires and library materials. Questionnaires were distributed to 40 people as samples and the results were managed and analyzed. The author found several facts in the field, some of which can be concluded, after the availability of free wifi access, youth began to be preoccupied with their respective gadgets, and the culture of Maghrib Koran has begun to disappear, in social matters that previously helped each other and worked hand in hand, now starting being indifferent, so that the socio-religious youth after the existence of the internet, especially free wifi, experienced a decline and decline.